Isobaric levobupivacaine for intrathecal anesthesia as an effective and safe option in transurethral resection of the prostate surgery - Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Nada, I Ketut Wibawa; Astuti, Mira Kusuma (Bali Journal of Anesthesiology, 2019)
The search for safer anesthetic solutions has always been one of the primary needs in anesthesiology practice. Levobupivacaine, the pure S (-) enantiomer of bupivacaine, emerged as a safer alternative for intrathecal anesthesia than its racemic parent (bupivacaine). Levobupivacaine shows a lower risk of the central nervous system and cardiovascular toxicity.However, in many countries, levobupivacaine is only available in isobaric solution, where the isobaric solution for intrathecal anesthesia is still often be questioned its effectiveness because of the fear that the block spreading is unpredictable. In this case series, we describe sensory and motor block characteristics, hemodynamics profile and adverse effects of isobaric levobupivacaine in intrathecal anesthesia for six patients with American Society of Anesthesiology physical status II-III whose undergo transurethral endoscopic surgery.